External validation of a refined four-stratum risk assessment score from the French pulmonary hypertension registry. Issue 6 (30th June 2022) - Boucly, Athénaïs; Weatherald, Jason; Savale, Laurent; de Groote, Pascal; Cottin, Vincent; Prévot, Grégoire; Chaouat, Ari; Picard, François; Horeau-Langlard, Delphine; Bourdin, Arnaud; Jutant, Etienne-Marie; Beurnier, Antoine; et al.
Introduction: Contemporary risk assessment tools categorise patients with pulmonary arterial hypertension (PAH) as low, intermediate or high risk. A minority of patients achieve low risk status with most remaining intermediate risk. Our aim was to validate a four-stratum risk assessment approach categorising patients as low, intermediate-low, intermediate-high or high risk, as proposed by the Comparative, Prospective Registry of Newly Initiated Therapies for Pulmonary Hypertension (COMPERA) investigators. Methods: We evaluated incident patients from the French PAH Registry and applied a four-stratum risk method at baseline and at first reassessment. We applied refined cut-points for three variables: World Health Organization functional class, 6-min walk distance and N-terminal pro-brain natriuretic peptide. We used Kaplan–Meier survival analyses and Cox proportional hazards regression to assess survival according to three-stratum and four-stratum risk approaches. Results: At baseline (n=2879), the four-stratum approach identified four distinct risk groups and performed slightly better than a three-stratum method for predicting mortality. Four-stratum model discrimination was significantly higher than the three-stratum method when applied during follow-up and refined risk categories among subgroups with idiopathic PAH, connective tissue disease-associated PAH, congenital heart disease and portopulmonary hypertension. Using the four-stratum approach, 53% of patients changed risk category from baseline compared to 39% of patients when applying the three-stratum approach. Those who achieved or maintained a low risk status had the best survival, whereas there were more nuanced differences in survival for patients who were intermediate-low and intermediate-high risk. Conclusions: The four-stratum risk assessment method refined risk prediction, especially within the intermediate risk category of patients, performed better at predicting survival and was more sensitive to change than the three-stratum approach. A four-stratum risk assessment method with low, intermediate-low, intermediate-high and high risk categories was better at discriminating survival in pulmonary arterial hypertension than a three-stratum method with low, intermediate and high risk groups https://bit.ly/3mA6kj7